Toxicity of high salinity tannery wastewater and effects on constructed wetland plants - Calheiros, Cristina S. C. (2013)
The toxicity of high salinity tannery wastewater produced after an activated sludge secondary treatment on the germination and seedling growth of Trifolium pratense, a species used as indicator in toxicity tests, was evaluated. Growth was inhibited by wastewater concentrations >25% and undiluted effluent caused a complete germination inhibition. Constructed wetlands (CWs) with Arundo donax or Sarcocornia fruticosa were envisaged to further polish this wastewater. Selection of plant species to use in CWs for industrial wastewater treatment is an important issue, since for a successful establishment they have to tolerate the often harsh wastewater composition. For that, the effects of this wastewater on the growth of Arundo and Sarcocornia were assessed in pot assays. Plants were subject to different wastewater contents (0/50/100%), and both were resilient to the imposed conditions. Arundo had higher growth rates and biomass than Sarcocornia and may therefore be the preferred species for use in CWs treating tannery wastewater. CWs planted with the above mentioned plants significantly decreased the toxicity of the wastewater, as effluent from the CWs outlet stimulated the growth of Trifolium at concentrations <50%, and seed germination and growth even occurred in undiluted effluent.